Bacterial Composition, Genotoxicity, and Cytotoxicity of Fecal Samples from Individuals Consuming Omnivorous or Vegetarian Diets - Federici, Ermanno; Prete, Roberta; Lazzi, Camilla; Pellegrini, Nicoletta; Moretti, Massimo; Corsetti, Aldo; Cenci, Giovanni (Frontiers in Microbiology, 2017)
This study analyzes the composition of viable faecal bacteria and gut toxicology biomarkers of twenty-nine healthy volunteers, who followed omnivorous, lacto-ovo-vegetarian or vegan diets. In particular, the research was focused on the prevalence of some representative viable bacteria from the four dominant phyla (Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria) commonly present in human faeces, in order to evaluate the relationship between microorganisms selected by the habitual dietary patterns and the potential risk due to faecal water genotoxicity and cytotoxicity, considered as biomarkers for cancer risk and protective food activity. The relative differences of viable bacteria among dietary groups were generally not statistically significant. However, compared to omnivores, lacto-ovo-vegetarians showed low levels of total anaerobes. Otherwise, vegans showed total anaerobes counts similar to those of omnivores, but with lower number of bifidobacteria and the highest levels of bacteria from the Bacteroides-Prevotella phyla. Faecal water genotoxicity of lacto-ovo-vegetarians resulted significantly lower either in relation to that of omnivores and vegans. Lacto-ovo-vegetarians also showed the lowest levels of cytotoxicity, while the highest were found for vegans. These results highlighted that lacto-ovo-vegetarian diet was particularly effective in a favorable modulation of microbial activity, thus contributing to a significant reduction of the genotoxic and cytotoxic risk in the gut.